(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
A total of 72 mice were used for an experimental model of intestinal amoebiasis developed in the Swiss albino mice dividing into three groups, experimental immunocompetent mice group (Group-A), experimental immunodepressed mice group (Group-B) and control group (Group-C). The inoculum (106 cells of Entamoeba histolytica/0.2 ml of medium) was used to inoculate into the caecum of the experimental groups of mice in the ICDDR,B laboratory, Dhaka. The mice were sacrificed at 5, 10, 15, 20, 25 and 30th days after inoculation for observation of caecal lesions and gross pathologic changes and histopathological analysis. The animals in the experimental two groups and control did not develop any caecal amoebiasis. The culture results of the stool of the mice which were inoculated with the inoculum of E. histolytica were found to be positive on the first 10 days after post caecal inoculation. After 10 days, the culture results were negative and the antiamoebic antibody levels of all animals were also found negative. DOI: http://dx.doi.org/10.3329/jbas.v38i2.21341 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 2, 167-175, 2014